SISTEM REKOMENDASI MAKANAN MULTI – KRITERIA UNTUK KONSUMEN DENGAN ANGGARAN TERBATAS MENGGUNAKAN ALGORITMA CONTENT BASED FILTERING - Azhar, Raniah; Shidqin, Dhuha Shobiyan; Prakoso, Azzam Ade; Rakhmah, Syifa Nur; Sariasih, Findi Ayu; Sutoyo, Imam (STMIK KAPUTAMA, 2026)
ABSTRACTThe primary challenge in current digital recommendation services is aligning product quality with the economic constraints of the user. This study focuses on the development and implementation of a Food Recommendation System operating on Multi-Criteria, namely Maximum Budget (Price) and Quality (Predicted Rating). The methodology applied is Content-Based Filtering, where the system analyzes nutritional content data and the estimated ingredient cost of each menu to determine the level of compatibility with the user’s preference profile. The processing flow begins with receiving a price limit set by the consumer, followed by a strict filtering phase to exclude menus outside the budget, and subsequently ranking the qualified menus based on the quality score generated by a Machine Learning model. This implementation successfully delivers ordered and cost-efficient menu recommendations, demonstrating its high potential as an effective assistant in supporting food purchasing decisions for consumers facing financial limitations.Keywords: Recommendation System, Multi-Criteria, Budget Constraint, Content-Based Filtering, Predicted Rating.